Pore engineering of hierarchically structured hydrodemetallization catalyst pellets in a fixed bed reactor. (20th July 2019) - Shi, Yao; Ye, Guanghua; Yang, Changfeng; Tang, Yanqiang; Peng, Chong; Qian, Gang; Yuan, Weikang; Duan, Xuezhi; Zhou, Xinggui
Highlights: Pore structures of HDM catalyst pellets were optimized at the reactor scale. Reactor-pellet coupling model based on hierarchical pore structures was adopted. Relationship of the diffusivity with the macropore structure was established. Mesopore-dependent concentration gradient along the reactor was proposed. Abstract: Probing the effects of hydrodemetallization (HDM) catalyst pore structures is of great importance. In this work, the pore structures of hierarchically structured HDM catalyst pellets are optimized based on a Random Spheres Model at the reactor scale. Understanding of the metal deposition behaviors and the concentration profiles along the reactor indicates strong macropore-dependent catalyst pellet utilization and mesopore-dependent bed utilization, respectively. Subsequently, relationships of the effective diffusivity with the macropore structure and the concentration gradient along the reactor with the mesopore structure are proposed, and the effects of the macro-/mesopore diameters and porosity are studied to maximize the exit conversion and catalyst lifetime. Our optimized results not only are superior to previously optimized results, but also provide rational interpretations for previous experimental observations. The insights revealed here could shed new light on the rational pore engineering of the hierarchical structured HDM catalysts.